SYNTHESIS, CHARACTERIZATION AND ANTIOXIDANT ACTIVITY OF 2-ARYL BENZOTHIAZOLE DERIVATIVES - Amin, Shaista; Parle, Amrita (International Journal of Current Pharmaceutical Research, 2018)
Objective: To synthesize benzothiazole derivatives, characterize them by 1HNMR and ATIR techniques and evaluate for their antioxidant activity. Methods: In the present study 12 benzothiazole derivatives were synthesized by reacting 2-chloronitro benzene as the primary reactant with different aromatic aldehydes and benzoic acids. Reactions were monitored using thin layer chromatography technique, and the newly synthesized derivatives were characterized by ATIR and 1HNMR techniques. The antioxidant assay was performed using 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) or ABTS method and 2,2-diphenyl-1-picrylhydrazyl or DPPH method. Results: The antioxidant activity was found to be better in ABTS assay than DPPH assay. The compounds showed comparable activity to ascorbic acid at 100Âµg/ml. Conclusion: It was found that the synthesized benzothiazole derivatives showed significant radical scavenging potential.